Mahabbah Concept According to Abu Hamid Muhammad Al-Ghazali - Ahmad Arif; Muhammad Nur Amin; Eka Prasetiawati (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
According to Sufi thought, every step we take in life is an opportunity to learn more about God and become closer to him. Serious believers in God have a decision between the following three paths, each of which is informed by one of the three fundamental capabilities of the human mind. If a person is willing to put in their best effort, they will engage in jihad (mujahid) and seek martyrdom in the sake of Allah SWT. If he uses his mind to its fullest capacity, he may engage in ijtihad and become closer to God's truth via inference. If he puts out his best spiritual effort, he will engage in mujahadah in order to deepen his devotion to God. following the teachings of Abu Hamid Muhammad Al-Ghazali. QS Surah Al-Imran [2]:31 and Al-Baqarah [3]:165 explain mahabbah, although they don't go into great depth about the many steps involved. Humans are encouraged to be able to carry out the obligations of Muslims because this will bring us close to Allah SWT. This verse is included in the hubbun chapter of the book of tafsir arba'in fi usul al-din, where he explains that the ultimate love is only Allah with us carrying out his commands and staying away from his prohibitions, then this is clear evidence of our love for him. The approach is a socio-historical character analysis that employs the author's tafsir book as an analytical knife. Findings are presented in the guise of an explanation of the Arabic term mahabbah, which means